Medication use in people with late stage Parkinson's disease and parkinsonism living at home and in institutional care in north-east England: A balance of symptoms and side-effects?. (November 2016) - Hand, Annette; Gray, William K.; Oates, Lloyd L.; Woolford, Megan; Todd, Anna; Bale, Elizabeth; Jones, Catherine; Wood, Brian H.; Walker, Richard W.
Abstract: Background: People with Parkinson's disease (PD) and parkinsonism living in care homes (residential or nursing care) in the UK represent around 10–15% of all people with PD and 3–5% of all care home residents. There are few previous data on medication use in those living in care homes with PD. In this study we aimed to compare medication use in a representative cohort of people with PD living in care homes in north-east England with those living in their own homes. Method: All people with late stage (Hoehn and Yahr III-V) idiopathic PD, PD dementia, or atypical parkinsonian syndromes under the care of the Northumbria Healthcare NHS Foundation Trust PD service on 1st January 2015 were identified. Demographic, disease characteristics and medication use data were collected from an audit of medical notes of all those identified. Results: We identified 377 people who met the inclusion criteria, 91 (24.1%) of whom were living in a care home. Disease stage, age and age at disease onset were all significantly higher and levodopa equivalent dose significantly lower in those living in care homes, although disease duration and levodopa dose were not. Greater age, lower levodopa equivalent dose and higher disease stage were independently associated with being in a care home. Conclusions: Although people in care homes had more advanced disease, they were on a significantly lower levodopa equivalent dose. This is likely to be due to the requirement to balance symptom management with drug side-effects. Highlights: Ninety-one patients were living in a care home and 286 in their own home. Levodopa equivalent dose (LED) was lower in care home than own home patients. Age, LED and disease stage were associated with care home residence. Disease duration did not predict care home residence.